Antibiotic susceptibility of bacterial isolates and water quality index of water sourced from closed ground water and open hand dug well in Koko Community, Delta State, Nigeria - IMARHIAGBE, Emmanuel Esosa; IKHAJIAGBE, Beckley (Studia Universitatis Babeș-Bolyai Biologia, 2018)
Water samples were collected from a semi urban community in Nigeria with the aim of investigating the water quality index and antibiotic profile of bacterial isolates of closed ground water and open hand dug wells. Physicochemical and microbiological analyses were carried out using standard analytical methods. pH of groundwater and hand dug well ranged from 4.16 to 5.74 and 4.83 to 5.22 respectively. The total suspended solid of water samples for hand dug well ranged from 1.2-9.2mg/l. Also iron concentrations for groundwater and hand dug well water samples ranged from 0.15-0.54 mg/l and 0.62-1.12 mg/l respectively. Microbial analysis of the water samples revealed the presence of bacteria such as S. aureus, Klebsiella sp., E. coli, B. subtilis, Pseudomonas, Aeromonas hydrophila and Enterobacter aerogenes and fungi such as Aspergillus niger, Penicillium notatum, Aspergillus flavus, Rhizopus stolonifer and Saccharomyces cerevisiae. The total heterotrophic bacterial count of water samples for groundwater and hand dug well samples indicated that values ranged from 2.9 - 4.4 ×103 cfu/ml and 5.4 – 8.6 ×103 cfu/ml respectively. Total coliform of water samples for groundwater and hand dug well samples indicated that values ranged from 5-8 MPN/100ml and 10-20 MPN/100ml respectively. E. coli count of water samples for groundwater and hand dug well samples indicated that values ranged from 0.0 MPN/100ml and 4-8 MPN/100ml respectively while total fungal count of groundwater and hand dug well samples indicated that values ranged from 0.0 - 6.0×102 cfu/ml and 3.5×102-17.0×103 cfu/ml respectively. Variable antibiotic susceptibility patterns were observed in antibiotic inhibitory zone (mm) among the tested bacterial isolates. Evaluation of Water Quality Index indicated values of 34.4 for groundwater source indicating good water quality and 67.31 for open hand dug well indicating water was of poor quality. Findings from this study revealed that groundwater sources had better and acceptable quality compared to those of open hand dug wells, hence it is recommended that critical measures be put in place to ensure the safety of both sources of water in Koko community.